Ge epitaxial films on GaAs (100), (110), and (111) substrates for applications of CMOS heterostructural integrations - Tang, Shih-Hsuan; Kuo, Chien-I; Trinh, Hai-Dang; Chang, Edward Yi; Nguyen, Hong-Quan; Nguyen, Chi-Lang; Luo, Guang-Li (My University, 2013)
Epitaxial Ge films were grown on GaAs (100), (110), and (111) substrates by using ultra-high vacuum chemical vapor deposition and studied with various methods. The incubation times and growth rates were quite different for these three GaAs substrates because the surface arsenic coverage on GaAs and hydrogen desorption energy on Ge are different for each orientation. High-resolution x-ray diffraction measurements, direct band-gap emission of photoluminescence measurements, and cross-sectional transmission electron microscopy showed that the Ge films had high crystal quality, low defect density, and sharp Ge/GaAs interfaces. In this study, atomic force microscopy analysis found that the Ge films grow on GaAs (100) and (111) via the Frank van der Merwe mode, while the Ge film grows on GaAs (110) via the Volmer-Weber mode at the initial growth stage, which can be explained by the thermodynamic theory of capillarity. Interestingly, when the thickness of the Ge film on the GaAs (110) substrate increases to similar to 220 nm, the 3D Ge islands merge and form a smooth surface (rms roughness of 0.3 nm), which is useful for devices. The authors also fabricated Ge metal-oxide-semiconductor capacitors (MOSCAPs) on GaAs (100) and (110) substrates. Both Ge/GaAs (100) and Ge/GaAs (110) MOSCAPs exhibit good capacitance-voltage responses with strong inversion behaviors, which means the grown material has reached device quality. The Ge/GaAs (110) structure especially offers optimal integration of Ge pMOSFETs on GaAs substrates because Ge (110) has a high hole mobility compared with Ge (100) and (111). (C) 2013 American Vacuum Society. [http://dx.doi.org/10.1116/1.4789427]